Indo-Pacific Maritime Cooperation: ASEAN Mechanisms on Security Towards Global Maritime Governance - Angel Damayanti (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Unair, 2019)
The importance of the sea in the current era of globalization has called all countries for managing their interests at sea as well as their common concern collectively, cooperatively and inclusively. By looking at the notions of the sea as a medium of connectivity and sea as a resource coupled with its vulnerability particularly in Indian and Pacific Oceans, Indo-Pacific maritime cooperation towards global ocean governance accordingly are vital to the international stability, a successful of sea-based trading system and sustainability use of the oceans. Therefore this article discusses the rationale of Indo-Pacific Maritime Cooperation, which made possible by the common concern of countries that locate between the Indian and West Pacific ocean maritime, the vulnerabilities of the region and the existence of various ASEAN’s mechanisms on Maritime Security Cooperation as well as regional regime and international law. Nevertheless, ASEAN needs to note some issues relating to its consolidation as well as the internal challenges in the realization of global maritime governance.